Resonances of planetarity and commons within evolving urbanisms - Tarmo Pikner (Fennia: International Journal of Geography)
This essay explores urbanism in relation to earthly and planetary concerns as relational processes in which the roles of humans and the sustaining of life forms are negotiated and transformed. The guiding question is: how do urbanites resonate with significant environmental matters while intersecting diverse disturbances, commons, and anticipated futures? The resonances of the planetary within urban change are examined through three vignettes about coastal assemblages involving waste, birds, and energy. These vignettes, related to the Baltic Sea and its diverse publics, illustrate how urbanisation interacts with voluminous spaces and emergent commons. The essay highlights urban-environmental entanglements in which contested ideologies of nature and entangled care reshape understandings of environmental problems and solutions alongside significant changes in urbanism. Some zones of ignorance are extensively exploited in future transformations, yet these zones could also be transformed into spaces of nature-culture care and commons, pointing toward conviviality.